2010 IEEE International Conference on Management of Innovation &Amp; Technology 2010
DOI: 10.1109/icmit.2010.5492707
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of Swedish companies' offshoring of R&D activities to China

Abstract: A trend among manufacturing companies is offshoring of R&D. The aim of this study is to investigate Swedish companies' offshoring of R&D activities to China, utilizing both a survey and explorative case studies. The survey results show that 9% of the companies have offshored R&D to China, that performance in China is satisfactory, primarily in terms of costs, and that there is a need for strong integration mechanisms to handle coordination and information sharing. Based on the case studies, a categorization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Description of softgoal Balanced [Asset Sharing] Quantity of contents transferred must be equal among partners [46].…”
Section: Evaluation Phasementioning
confidence: 99%
“…Description of softgoal Balanced [Asset Sharing] Quantity of contents transferred must be equal among partners [46].…”
Section: Evaluation Phasementioning
confidence: 99%
“…Therefore, irrespective of where the facilities are located within a company's international manufacturing network, the management of manufacturing activities is critical for the success of the international operation. For example, the coordination in purchasing makes it possible to achieve the economies of scale in purchasing, and the transfer of experience can increase the know-how especially within the development centers [18]. For what concerns the management of international operations to facilitate coordination, Rudberg and Olhager [9] presented four coordination approaches corresponding to four basic network configurations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As this subtler mechanism is an intangible approach, i.e., this cannot readily be installed in an organization; its success depends on continuous relationships between facilities. Likewise, it has been demonstrated that communication, as a means of informal coordination, between the host facility and the headquarters is crucial for the success of offshore (knowledge-intensive) activities [18].…”
Section: Mechanisms Of Coordinationmentioning
confidence: 99%
“…this cannot readily installed in an organisation, its success depends on continuous relationships between facilities. Likewise, it has been demonstrated that communication, as a means of informal coordination, between the host facility and the headquarters is crucial for the success of offshore (knowledge-intensive) activities (Hafström et al, 2010).…”
Section: Mechanisms Of Coordinationmentioning
confidence: 99%